PENDAMPINGAN PENGELOLAAN KEUANGAN PADA JEMAAT GKI DIASPORA KOTARAJA - Patiran, Andarias; Boari, Yoseb; Dasinapa, Margaretha B.; Marani, Yohanes; Panggabean, Bungaria (Fokus ABDIMAS, 2023)
Financial management is a process that involves planning, organizing, supervising, controlling and reporting financial activities carried out by individuals, families, organizations or government agencies. The purpose of this financial management assistance is to improve the ability of cash holders. The method of implementing this service is to provide training and assistance to cash holders. The results of this service activity are 1). Cash holders and congregation managers need a better understanding of financial management and ways to overcome common obstacles. 2). There needs to be assistance in managing the congregation's finances in order to increase the effectiveness and efficiency of financial management for cash holders. 3). It is necessary to make clear financial management very important to ensure that the congregation's finances are well managed. 4). Mentoring activities can help improve the performance of cash holders and congregation managers in managing finances.Keywords: Financial Management, Financial Oversight, Financial Reporting